Perbandingan Metode Pembelajaran Quran: Metode Asy Syifa’ dan Dirosa di Dua Lembaga - Abror Dikna Anugrah; Muh. Nur Rochim Maksum; Mohamad Ali (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to compare two Qur'an reading methods implemented in different institutions: the Asy Syifa' Method at Alima Quran House and the Dirosa Method at the Omah Ngaji Berbagi Community Islamic Boarding School. Using a descriptive qualitative approach, the research explores how each method is implemented, identifies their respective strengths and weaknesses, and assesses their impact on students' Qur'an reading abilities. Data collection involved direct observation, in-depth interviews with teachers and students, and documentation of learning activities. The research subjects consisted of students and instructors from both institutions. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. Findings indicate that the Asy Syifa' Method has a structured, level-based curriculum (Tahsin A–D) supported by regular evaluations such as mid- and end-semester tests. This method effectively enhances students' accuracy in reading the Qur'an, particularly in mastering tajweed and makhrajul huruf. In contrast, the Dirosa Method provides a simpler and more time-efficient learning experience, comprising only 20 sessions, making it suitable for adult beginners aiming to quickly gain basic Qur'an reading skills. However, this method lacks systematic evaluation and in-depth tajweed instruction. In conclusion, both methods offer distinct advantages depending on the learners’ needs: the Asy Syifa' Method suits those seeking structured, in-depth mastery, while the Dirosa Method benefits those requiring flexible, rapid learning. These findings are expected to inform educators and Islamic learning institutions in selecting appropriate Qur'an teaching methods based on their students’ profiles and learning objectives